Circuits and architectures for field programmable gate array with configurable supply voltage. - Lin, Y. (IEEE Transactions on VLSI systems)
Field programmable gate arrays (FPGAs) with supply voltage (Vdd) programmability have been proposed recently to reduce FPGA power, where the Vdd-level can be customized for FPGA circuit elements and unused circuit elements can be power-gated. In this paper, we first design novel Vdd-programmable and Vdd-gateable interconnect switches with minimal number of configuration SRAM cells. We then evaluate Vdd-programmable FPGA architectures using the new switches. The best architecture in our study uses Vdd-programmable logic blocks and Vdd-gateable interconnects. Compared to the baseline architecture similar to the leading commercial architecture, our best architecture reduces the minimal energy-delay product by 54.39% with 17% more area and 3% more configuration SRAM cells. Our evaluation results also show that LUT size 4 gives the lowest energy consumption, and LUT size 7 leads to the highest performance, both for all evaluated architectures.